2013
DOI: 10.2174/1874434601307010149
|View full text |Cite
|
Sign up to set email alerts
|

Vocation, Friendship and Resilience: A Study Exploring Nursing Student and Staff Views on Retention and Attrition

Abstract: Introduction:There is international concern about retention of student nurses on undergraduate programmes. United Kingdom Higher Education Institutions are monitored on their attrition statistics and can be penalised financially, so they have an incentive to help students remain on their programmes beyond their moral duty to ensure students receive the best possible educational experience.Aims:to understand students’ and staff concerns about programmes and placements as part of developing our retention strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
4
40
0
Order By: Relevance
“…Resilience contributed to nursing students' meeting their challenges and academic goals (Carroll, 2011;Williamson, Health, & Proctor-Childs, 2013). However, despite the growing number of studies of nursing students' resilience, there remains limited description of nursing students' resilience, particularly their understanding and enactment of resilience.…”
Section: Resilience As a Stress Mitigatormentioning
confidence: 99%
See 4 more Smart Citations
“…Resilience contributed to nursing students' meeting their challenges and academic goals (Carroll, 2011;Williamson, Health, & Proctor-Childs, 2013). However, despite the growing number of studies of nursing students' resilience, there remains limited description of nursing students' resilience, particularly their understanding and enactment of resilience.…”
Section: Resilience As a Stress Mitigatormentioning
confidence: 99%
“…As described in the studies, nursing students and nurse educators faced significant challenges that required them to have resilience. For example, resilience was demonstrated through students' perseverance with their challenges, which then was a contributing factor in facilitating success in their nursing education and in the completion of their degrees (Carroll, 2011;Williamson, Health, & Proctor-Childs, 2013). Carroll (2011) found that students described resilience as having the determination to succeed rather than retreating in the face of challenges.…”
Section: Resilience Is Important In Nursing Educationmentioning
confidence: 99%
See 3 more Smart Citations